Pengaruh Kecepatan Angin dan Sudut Blade terhadap Unjuk Kerja Turbin Angin Poros Vertikal Tipe Savonius Duabelas Blade - Elfridus Bruno Lake; Muhamad Jafri; Nurhayati Nurhayati (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2015)
ABSTRACT This study aimed to determine the effect of wind speed and Blade angle Performance against Vertical Axis Wind Turbine Blade Savonius type. This study is a model made of type Savonius wind turbine blade in a laboratory scale. Dimensions tusrbin Savonius is a diameter of 0.1 meters and height of 0.1 meter, with a vertical rotor position (to facilitate the testing process), so it is assumed the direction of the air flow does not change and lead to the rotor which can be set when testing. The research method is an experiment, by variation of Blade angle -50, 00, 50 and 100. Variations in wind speed of 3.40 m/s, 4.35 m/s and 5.33 m/s. The testing procedure: Each model Savonius turbine rotor blade totaling 12 pieces assembled on Blade holder with angle -50, 00, 50 and 100. Each circuit is then mounted on the stand turbine located at one end of the tunnel and at the other end of the tunnel placed fan, turbine shaft is connected to a pulley as a hanging load. The fan is turned on. After a stable rotation, the wind speed is measured using the anemometer. The results of the research through variations of wind speed and angle of the blade on the performance of vertical axis wind turbine Savonius type, the variation of wind speed of 3.4 m/s, 4.35 m/s and 5.33 m/s showed best performance in blade angle of -50. Performance on the turbine blade angle variation of 00, 50, and 100 to the blade angle -50 occur an average increase of 70.47% power coefficient. The highest maximum output power is 0.282391 Watts (power coefficient of 0.310827), with 274.8864 rotor rpm, and torque variation occurs in 0.00981 Nm -50 blade angle and wind speed 5.33 m / s. Lowest maximum output power is 0.013548 Watts (power coefficient of 0.057451), with 0.000981 Nm torque on the rotor rotation occurs at 131.883 rpm and 50 and the blade angle variation of wind speed of 3.4 m/s by a margin of 84.4% of the highest maximum output power is obtained at an angle of -50 blade.